2021
DOI: 10.35848/1882-0786/abf763
|View full text |Cite
|
Sign up to set email alerts
|

AlGaN-based UV-B laser diode with a wavelength of 290 nm on 1 μm periodic concavo–convex pattern AlN on a sapphire substrate

Abstract: Room-temperature pulsed oscillation with a laser wavelength of 290 nm and a threshold current density of 35 kA cm−2 was achieved by fabricating a UV-B laser diode on a thick AlGaN film formed on a 1 μm periodic concavo–convex pattern AlN (PCCP-AlN) on a sapphire substrate. The advantage of this method using PCCP-AlN is that it promotes the nucleation of AlGaN crystals. Planarization of this growth nucleus with AlGaN reduces the threading dislocation density at the top of the AlGaN growth layer while suppressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…This gap has a distinct correlation with threading dislocation densities typical for AlGaN alloys, which were shown in Figure 1 of the review reported in [ 24 ]. This correlation reveals a very critical effect of threading dislocation density (TDD) on the threshold current density of DUV-LDs, which was further confirmed by direct measurements reported in [ 25 , 28 , 29 , 30 ], see Figure 2 a (TDD for the lowest threshold current density shown in this figure was not reported in [ 25 ], but we estimated TDD in the range of ~10 6 –10 7 cm −2 ). The efforts aimed at TDD reduction, thus improving the threshold current density, will be discussed in more detail in Section 2 .…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…This gap has a distinct correlation with threading dislocation densities typical for AlGaN alloys, which were shown in Figure 1 of the review reported in [ 24 ]. This correlation reveals a very critical effect of threading dislocation density (TDD) on the threshold current density of DUV-LDs, which was further confirmed by direct measurements reported in [ 25 , 28 , 29 , 30 ], see Figure 2 a (TDD for the lowest threshold current density shown in this figure was not reported in [ 25 ], but we estimated TDD in the range of ~10 6 –10 7 cm −2 ). The efforts aimed at TDD reduction, thus improving the threshold current density, will be discussed in more detail in Section 2 .…”
Section: Introductionsupporting
confidence: 89%
“… ( a ) Experimental threshold current densities of UV laser diodes (symbols) fabricated by various approaches, including growth on concave-convex patterned AlN (PCCP AlN) vs. TDD [ 25 , 28 , 29 , 30 ]; the straight line approximates the data. ( b ) Measured internal quantum efficiency (symbols) of UV-LEDs emitting at various wavelengths as a function of TDD in the LED structure [ 31 , 32 , 33 ]; the solid line is the theoretical curve calculated by the model described in [ 34 ].…”
Section: Figurementioning
confidence: 99%
“…It has also been reported that the density of micrometer‐sized V‐shaped pits and hillocks, which are formed on a wafer surface after device structure stacking, fabricated using the AlN nanopillar method was lower than that fabricated using the spontaneous nucleation method. [ 21,24 ] In addition, the energization tests conducted on a number of devices have clearly confirmed the higher yield of laser oscillation using the AlN nanopillar method. [ 21 ] Furthermore, it has been reported that hillock depends strongly on the threshold current in UV‐C LDs fabricated on AlN substrates, and this has a significant impact on device performance.…”
Section: Introductionmentioning
confidence: 96%
“…Thus, UV-B LDs have been fabricated on lattice-relaxed high-quality AlGaN template, in which a lattice-relaxing thickness film is stacked on the AlN underlayer and dislocations introduced during lattice relaxation are minimized by using the method. [17] Two methods of fabricating the AlGaN templates suitable at RT have been reported, namely, the spontaneous nucleation [20,22,23] and AlN nanopillar, [21,24] and the achievable dislocation density is slightly lower in the AlN nanopillar method. [21] Meanwhile, it is difficult to find a clear difference for the J th of LDs, specifically when only the top data are compared.…”
Section: Introductionmentioning
confidence: 99%
“…Here, a UV-B laser diode was fabricated through two breakthroughs: the use of relatively high-quality AlGaN with lattice relaxation [11,12] and the application of polarization doping [13,14] to the p-AlGaN cladding layer to achieve favorable optical cavity formation and high-current-density injection. To improve the performance of the fabricated UV-B laser diode, we have optimized the growth conditions of spontaneously nucleated AlN, [15] applied AlN nanopillars, [16,17] increased the optical confinement factor Γ, [18] and applied a refractive index waveguide structure. [19] Meanwhile, UV-B laser diodes use a combination of Cl 2 -inductively coupled plasma (ICP) dry etching and wet etching with the TMAH solution to form flat m-plane facets, [20] which are then used as mirrors.…”
mentioning
confidence: 99%